Characterization of morphology and physicochemical properties of native starches isolated from 12 Lycoris species. (30th June 2020) - Li, Kehu; Li, Qingzhu; Jin, Can; Narayanamoorthy, Shwetha; Zhang, Tongze; Sui, Zhongquan; Li, Zijun; Cai, Youming; Wu, Kao; Zhang, Yongchun; Corke, Harold
Highlights: Bulb starch of 13 Lycoris genotypes was characterized. 13 lycoris starches had either C-type or CA -type crystallinity. Lycoris starches had high amylose content and low gelatinization temperature. The starch granular size varied widely among Lycoris genotypes. Inter-relationships among 18 parameters of starch quality was analyzed. Abstract: In this study, starch was isolated from 13 genotypes of 12 Lycoris species, and the morphology, granule size distribution and physicochemical properties, including apparent amylose content (AAC), Rapid Visco Analyzer (RVA) pasting properties, textural properties, thermal and retrogradation properties were characterized. The majority of starch granules of the 13 Lycoris genotypes were oval in shape, and granule size followed a normal distribution with a mean diameter of 20–30 μm. Contrary to previously published findings, the XRD results revealed that lycoris starches had either C-type or CA -type crystallinity. All lycoris starches showed high AAC varying from 25.6% to 32.7%, and low gelatinization temperature (GT) ranging from 58.8 to 69.7 ℃. Inter-relationships among 18 starch quality traits were analyzed based on correlation analysis. The present study provides information on lycoris starch characteristics which should serve as a useful guide for later studies on lycoris starch utilization in food and non-food industries.